Data Release 2 of S-PLUS: Accurate template-fitting based photometry covering ∼1000 deg2 in 12 optical filters. Issue 3 (2nd February 2022) - Almeida-Fernandes, F; SamPedro, L; Herpich, F R; Molino, A; Barbosa, C E; Buzzo, M L; Overzier, R A; de Lima, E V R; Nakazono, L M I; Oliveira Schwarz, G B; Perottoni, H D; Bolutavicius, G F; et al.
ABSTRACT: The Southern Photometric Local Universe Survey (S-PLUS) is an ongoing survey of ∼9300 deg 2 in the southern sky in a 12-band photometric system. This paper presents the second data release (DR2) of S-PLUS, consisting of 514 tiles covering an area of 950 deg 2 . The data has been fully calibrated using a new photometric calibration technique suitable for the new generation of wide-field multifilter surveys. This technique consists of a χ 2 minimization to fit synthetic stellar templates to already calibrated data from other surveys, eliminating the need for standard stars and reducing the survey duration by ∼15 per cent. We compare the template-predicted and S-PLUS instrumental magnitudes to derive the photometric zero-points (ZPs). We show that these ZPs can be further refined by fitting the stellar templates to the 12 S-PLUS magnitudes, which better constrain the models by adding the narrow-band information. We use the STRIPE82 region to estimate ZP errors, which are ≲ 10 mmags for filters J0410, J0430, g, J0515, r, J0660, i, J0861 and z ; ≲ 15 mmags for filter J0378; and ≲ 25 mmags for filters u and J0395. We describe the complete data flow of the S-PLUS/DR2 from observations to the final catalogues and present a brief characterization of the data. We show that, for a minimum signal-to-noise threshold of 5, the photometric depths of the DR2 range from 19.1 to 20.5 mag (measured in Petrosian apertures), depending on the filter. The S-PLUS DR2 can be accessed from the website: https://splus.cloud .